Parental Monitoring and Open Communication Strategies as Predictors of Adolescents' Social Media Use and Adjustment among undergraduates in Anambra State, Nigeria. - Mary Nneka Nwikpo; Azukaego Ifeoma Eluemuno; Victor Ugochukwu Ezeonwumelu; Christopher Obinna Alaribe (Asosiasi Asesmen Pendidikan (AAP), 2025)
The increasing immersion of children and young adults in social media has heightened concerns about their psychosocial adjustment, underscoring the critical role of parental monitoring and communication. This study investigated how parental involvement, through monitoring and open communication, predicts social media use and adjustment among undergraduates in Anambra State, Nigeria. A correlational survey design was employed. Data were collected from 269 undergraduates (134 males, 135 females), aged 17 to 24 years, purposively selected from two public universities. The 24-item Parental Monitoring and Communication Questionnaire (PMCQ), culturally adapted and revalidated by experts, was used for data collection. Analyses were conducted using descriptive statistics, simple linear regression, and multiple regressions via SPSS version 25. Parental monitoring negatively predicted social media use (β = –0.29, R² = .084, p < .001) and positively predicted adolescent adjustment (β = 0.34, R² = .116, p < .001). Similarly, open communication negatively predicted social media use (β = –0.23, R² = .053, p < .001) and positively predicted adolescent adjustment (β = 0.31, R² = .096, p < .001). When combined, parental monitoring and open communication explained 11.6% of the variance in social media use and 17.2% in adolescent adjustment (p < .001), confirming their joint predictive strength. The findings reinforce the importance of autonomy-supportive parenting practices in the digital age. Implications include the need to enhance parents’ digital literacy, promote culturally sensitive communication, and encourage school-family collaboration. It is recommended that parenting workshops, school engagement programs, and policy frameworks be developed to support parents in guiding responsible social media use among Nigerian youth.